Movimiento obrero, política y literatura en la España contemporánea - Tuñón de Lara, Manuel, 1915-1997; Botrel, Jean-François (Colección I. T. S., 1974)
Participan: Manuel Tuñón de Lara, Casimiro Martí, Manuel González Portilla, Antonio M. Calero, Eugenio Lasa, Jacques Maurice, Alberto Gil Novales, Joaquín del Moral Ruiz, Manuel Aragón, Robert Marrast, Víctor Carrillo, Jean-François Botrel, Eloy Fernández Clemente, Juan Velarde Fuertes, José Luis Guereña.